PREFERÊNCIA DE LATERALIDADE DOS ESCOLARES DE 6 A 7 ANOS DE IDADE NAS ESCOLAS MUNICIPAIS DE IJUÍ/RS - Baiotto, Josiane C.; Llano, Débora C.; Pretto, Luciana M.; Bonamigo, Elenita C. B.; Winkelmann, Eliane R. (Salão do Conhecimento, 2013)
Resumo